Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.3389/fvets.2022.996015
|View full text |Cite
|
Sign up to set email alerts
|

Borrelia spirochetes in European exotic farm animals

Abstract: Ticks transmit a broad spectrum of pathogens, threatening both animal and human health. Tick survival and proliferation are strongly dependent on host selection and suitability. The hard tick Ixodes ricinus, which is widespread throughout most of Europe, is a host generalist capable of feeding on many different vertebrate species. Pasture-kept exotic farm animals may be at a high risk for tick and tick-borne pathogens infestations but research characterizing this is currently lacking. This study focused on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 57 publications
(59 reference statements)
0
4
0
Order By: Relevance
“…A few surveys ( n = 12) were conducted on buffaloes from South America [ 124 135 ] including Brazil (9), Colombia (2), and Argentina (1). The lowest number ( n = 4) of the eligible studies came from Europe [ 118 121 ]: Hungary (2), the Czech Republic (1), and Italy (1). Likewise, isolated surveys were conducted on buffaloes from North America (2), Cuba (1), and Mexico (1) (Additional file 1 : Table S1).…”
Section: Resultsmentioning
confidence: 99%
“…A few surveys ( n = 12) were conducted on buffaloes from South America [ 124 135 ] including Brazil (9), Colombia (2), and Argentina (1). The lowest number ( n = 4) of the eligible studies came from Europe [ 118 121 ]: Hungary (2), the Czech Republic (1), and Italy (1). Likewise, isolated surveys were conducted on buffaloes from North America (2), Cuba (1), and Mexico (1) (Additional file 1 : Table S1).…”
Section: Resultsmentioning
confidence: 99%
“…B. miyamotoi , initially identified and isolated in Japan in 1994 ( 50 ), is the causative agent of B. miyamotoi disease with generalized flu-like symptoms. Human cases of B. miyamotoi infection have been reported in European countries ( 51 , 52 ), the United States ( 53 , 54 ), Australia ( 55 ), and Japan ( 56 ). A survey of B. miyamotoi in Inner Mongolia suggested that 2.6% of I. persulcatus carried B. miyamotoi and 1.7% of patients bitten by ticks were infected with B. miyamotoi ( 57 ).…”
Section: Discussionmentioning
confidence: 99%
“…An important distinction needs to be made between animal infections, where the animal tissue tested positive for B. miyamotoi ( Table 3 ), and animal-associated tick infections, where the animal tissue was not tested, but the tick(s) attached to the animal tested positive for B. miyamotoi ( Table 4 ). Borrelia miyamotoi has also been detected in both birds and bird-associated ticks; however, there has been minimal follow-up research to interpret the role of birds in B. miyamotoi perpetuation and maintenance ( Table 3 and Table 4 ) [ 94 , 109 , 110 ].…”
Section: Animal Infectionsmentioning
confidence: 99%